Impacts of hydrogeological characters of fractured rock on thermodynamic performance of ground-coupled heat pump. - Hang Zou; Peng Pei; Jin Zhang (PLoS ONE)
Ground-coupled heat pump (GCHP) is used to recovery shallow geothermal energy, a widely distributed green energy source. Due to the imbalance between heat rejection and extraction, heat buildup underground is commonly associated with the long-term operation of GCHPs, which undermine system performance. Heat buildup intrinsically results the irreversibilities (entropy production) in subsurface heat sink, in which thermodynamic and transport properties are largely influenced by hydrogeologic properties, especially the existence of fractures and groundwater. This study investigates the influence of water flow in fractures on the thermodynamic performance of a single borehole heat exchanger (BHX) and heat buildup in the underground heat exchange zone (UHXZ). Potential influence factors were screened out, and new terms were proposed to quantify the scale of fractures and available heat and cold in the heat sink. Governing equations were established to calculate the impacts of vertical and horizontal fractures on the heat exchange rate in BHX as well as on the heat flow across the UHXZ. The analysis results show that water flow in fractures can significantly enhance heat transfer, reduce required number of boreholes, mitigate heat buildup and reduce irreversibilities underground. The results also suggest that the role of fracture scales and water velocity in GCHP operation should be carefully evaluated. Therefore, detailed hydrogeological survey is necessary. The study results provide a guide on more accurately evaluating the risk of heat buildup and how to take advantage of hydrogeological characters to improve the performance of GCHPs.